Alteration of drug metabolism in Gilbert's syndrome. Issue 8 (August 1976) - Carulli, N; Ponz de Leon, M; Mauro, E; Manenti, F; Ferrari, A
Abstract : The pathophysiology of Gilbert's syndrome was studied by investigating the metabolism of the drug tolbutamide, which is metabolised by the liver but does not undergo glucuronidation. Using rat liver cell supernatant, tolbutamide was shown to bind to the hepatic cytoplasmic Y protein in a manner similar to other organic anions, but not to Z protein. In 31 patients with Gilbert's syndrome the plasma disappearance (plasma half-life, mean +/- SD: 628+/-84 min) and metabolic clearance (7-9+/-1-8 ml/min) were significantly (P less than 0-0005) altered compared with the 13 controls (mean half-life 393+/-26 and mean clearance 13-4+/-1-5). The eight patients with hyperbilirubinaemia due to haemolytic disease showed no difference from the normal control subjects. In three patients with Gilbert's syndrome the cumulative urinary excretion of tolbutamide metabolites, 24 hours after the administration of the drug, was 30% lower than in the controls. In the five patients with Gilbert's syndrome, phenobarbital administration (100 mg/day) produced a significant increase in clearance of the drug from 8-8+/-0-8 to 13-4+/-1-9 ml/min; this was paralleled by a fall in serum bilirubin concentration. The plasma half-life of tolbutamide was similar in Gunn rats and Wistar rats. The results suggest that the metabolic defect(s) of Gilbert's syndrome affects compounds other than bilirubin and that defective uptake is probably the major factor.